2019
DOI: 10.1002/jlb.3vma0918-374r
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine from a biologic source regulates neutrophil extracellular traps (NETs)

Abstract: Neutrophil extracellular traps (NETs) are implicated in autoimmune, thrombotic, malignant, and inflammatory diseases; however, little is known of their endogenous regulation under basal conditions. Inflammatory effects of neutrophils are modulated by extracellular purines such as adenosine (ADO) that is inhibitory or ATP that generally up‐regulates effector functions. In order to evaluate the effects of ADO on NETs, human neutrophils were isolated from peripheral venous blood from healthy donors and stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Finally, A 3 ARs are involved in the formation and extension of filipodia-like projections in neutrophils, as shown by the selective agonist 2-chloro-N 6 -(3-iodobenzyl)-adenosine-5 -N-methyluronamide (Cl-IB-MECA), thus improving bacterial phagocytosis and chemotaxis [18]. Interestingly, Ado signaling is involved in the formation of the so-called Neutrophil Extracellular Traps (NETs), which are chromatin filaments coated with pro-inflammatory and effector molecules released by neutrophils into the extracellular space in response to inflammatory triggers [19]. NETs formation has the main role of containing pathogen spreading, but it has been also linked to autoimmune disorders, since their bioactive molecules can directly damage the extracellular matrix and amplify the immune response.…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, A 3 ARs are involved in the formation and extension of filipodia-like projections in neutrophils, as shown by the selective agonist 2-chloro-N 6 -(3-iodobenzyl)-adenosine-5 -N-methyluronamide (Cl-IB-MECA), thus improving bacterial phagocytosis and chemotaxis [18]. Interestingly, Ado signaling is involved in the formation of the so-called Neutrophil Extracellular Traps (NETs), which are chromatin filaments coated with pro-inflammatory and effector molecules released by neutrophils into the extracellular space in response to inflammatory triggers [19]. NETs formation has the main role of containing pathogen spreading, but it has been also linked to autoimmune disorders, since their bioactive molecules can directly damage the extracellular matrix and amplify the immune response.…”
Section: Innate Immunitymentioning
confidence: 99%
“…NETs formation has the main role of containing pathogen spreading, but it has been also linked to autoimmune disorders, since their bioactive molecules can directly damage the extracellular matrix and amplify the immune response. In this scenario, Ado has proven its ability to reduce NETs formation and the excessive so-called "NETosis", mostly via activation of A 2A ARs, thus contributing to down-regulate NET pro-inflammatory activity, and to counteract the development of autoimmunity [19].…”
Section: Innate Immunitymentioning
confidence: 99%
“…In their studies, Abbasi et al 210,211 showed that BM‐MSCs treated with caffeine at low to moderate concentrations promoted neutrophil survival, besides, to increase the phagocytosis and production of reactive oxygen species (ROS), when compared to MSCs not treated. Similarly, the CD73 inhibition in BM‐MSCs impairs the production of extracellular Ado and significantly reduces neutrophils' maturation and modulatory abilities 212 . Although these findings offer new insights into the immunomodulatory effects from MSCs through the adenosinergic pathway, the mechanism underlying these effects needs to be further clarified.…”
Section: Adenosinergic Signaling In Immunomodulatory Effects Of Mscsmentioning
confidence: 99%
“…The purinergic signaling system involves the release of ATP and adenosine to the extracellular milieu during cellular disturbances, both important controllers of the immune cell functions ( Burnstock and Verkhratsky, 2009 ; Antonioli et al., 2013 ; Virgilio and Vuerich, 2015 ; Cekic and Linden, 2016 ). In neutrophils, ATP induces neutrophil activation, but the accumulation of adenosine through extracellular ATP degradation can lead to considerable inhibitory and anti-inflammatory effects ( Antonioli et al., 2013 ; Xu et al., 2019 ). In addition, several studies reveal that this sequential dephosphorylation of ATP into adenosine (ATP > ADP > AMP > adenosine) is under control of ectonucleotidases, cell surface-located enzymes.…”
Section: Introductionmentioning
confidence: 99%